2020
DOI: 10.1002/1878-0261.12746
|View full text |Cite
|
Sign up to set email alerts
|

TERT C228T mutation in non‐malignant bladder urothelium is associated with intravesical recurrence for patients with non‐muscle invasive bladder cancer

Abstract: Telomerase reverse transcriptase ( TERT ) promoter mutations are frequently found in tumors or urine from patients with urothelial carcinoma (UC). TERT promoter mutations are also detected in urine from patients with no evidence of cancer but are associated with subsequent UC development. Mutations in the TERT promoter are thought to be present in nonmalignant urothelium (NMU) during early stages of tumor formation prior to pathological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…These mutations are identified in both the normal tissues, which may be precancerous lesion, and the tumor samples of bladder cancer including various rare histological variants (micropapillary, plasmacytoid, adenocarcinoma, squamous cell carcinoma) [ 21 , 22 , 23 , 24 , 25 , 26 ]. These mutations can also be detected with ease in both the pellet and cell-free DNA from patient urine samples, promising application in urine-based disease detection and prediction of progression [ 27 , 28 , 29 , 30 ].…”
Section: Representative Genetic Mutations In Bladder Cancermentioning
confidence: 99%
“…These mutations are identified in both the normal tissues, which may be precancerous lesion, and the tumor samples of bladder cancer including various rare histological variants (micropapillary, plasmacytoid, adenocarcinoma, squamous cell carcinoma) [ 21 , 22 , 23 , 24 , 25 , 26 ]. These mutations can also be detected with ease in both the pellet and cell-free DNA from patient urine samples, promising application in urine-based disease detection and prediction of progression [ 27 , 28 , 29 , 30 ].…”
Section: Representative Genetic Mutations In Bladder Cancermentioning
confidence: 99%
“…With Smoking being the most important risk factor, the proposed induced DNA damage from carcinogens within the urine or blood stream led to the idea of field cancerization but also DNA mutations occurring in non-malignant urothelium [5,12]. This observation was recently reported by Hayashi et al [13] identifying TERT promoter mutations in systematically collected normal urotheliums locating adjacent to non-invasive bladder tumor tissue. Additionally, even when the tumor was not mutated the associated normal urothelium showed a TERT promoter mutation.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, even when the tumor was not mutated the associated normal urothelium showed a TERT promoter mutation. Moreover, if TERT mutations were initially observed, positive associations with bladder recurrence after therapy were shown indicating a potential use of TERT promoter gene mutations as a biomarker [ 13 ]. In line with the above findings, in this present study we also identified specific TERT promoter mutations in tumor associated normal urothelium but also in non-invasive urothelial lesions adjacent to or non-adjacent to muscle invasive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the core promoter region of TERT cause telomerase reactivation in 60-80% of urothelial bladder tumors 13 . The TERT C228T mutation has been shown to be significantly associated with the prognosis of bladder cancer, particularly with bladder recurrence in NMIBC 14 , whereas TERT C250 mutation appears to be an independent predictive marker of response to BCG treatment 15 . However, in our series, neither C228T nor C250 mutation was associated with prognosis of NMIBC or response to BCG-therapy.…”
Section: Discussionmentioning
confidence: 99%